Titanium–oxo cluster reinforced gel polymer electrolyte enabling lithium–sulfur batteries with high gravimetric energy densities. Issue 2 (13th January 2021) - Pei, Fei; Dai, Shuqi; Guo, Baofu; Xie, Hao; Zhao, Chaowei; Cui, Jingqin; Fang, Xiaoliang; Chen, Chengmeng; Zheng, Nanfeng
Abstract : A titanium–oxo cluster-reinforced gel polymer electrolyte is developed to improve the performance of high-sulfur-loading lithium–sulfur batteries under lean electrolyte conditions. Abstract : Lithium–sulfur (Li–S) battery research has flourished by upgrading the performances of sulfur cathodes and Li metal anodes under flooded electrolyte conditions. However, since high gravimetric energy density can only be achieved at a low electrolyte/sulfur (E/S) ratio, the severe performance degradation under lean electrolyte conditions is becoming a bottleneck in the development of Li–S batteries. Here we propose a new class of gel polymer electrolytes by using titanium–oxo clusters as reinforcements to construct low E/S batteries. The developed electrolyte has favorable mechanical properties and high Li-ion conductivity, as well as excellent capabilities to block polysulfide shuttling and suppress Li dendrite formation, enabling low E/S batteries to exhibit enhanced capacities and cycling stabilities. Remarkably, the low E/S (3 μL mgS −1 ) battery fabricated with high sulfur loading (10 mgS cm −2 ) and low negative/positive capacity ratio (1/1) can deliver a gravimetric energy density of 423 W h kg −1 and continue to operate for 100 cycles. This study provides a new avenue for high-energy-density Li–S batteries.